Unraveling the immunomodulatory and metabolic effects of bioactive glass S53P4 on macrophages in vitro - Karoliina Kajander; Nicole Nowak; Negin Vaziri; Pekka K. Vallittu; Terhi J. Heino; Jorma A. Määttä (Journal of Materials Science: Materials in Medicine)
Abstract Macrophage metabolism is closely linked to their phenotype and function, which is why there is growing interest in studying the metabolic reprogramming of macrophages. Bioactive glass (BG) S53P4 is a bioactive material used especially in bone applications. Additionally, BG S53P4 has been shown to affect macrophages, but the mechanisms through which the possible immunomodulatory effects are conveyed remain unclear. According to the results presented here, the lipopolysaccharide (LPS) induced suppression in oxidative phosphorylation is rescued in macrophages cultured with BG S53P4 before the inflammatory stimulus. Additionally, BG S53P4-exposed macrophages expressed lower mRNA levels of inflammatory cytokines Il6 and Il1b, as well as demonstrated decreased activation of inflammatory interferon regulatory factor (IRF) and NF-κB pathways and nitrogen oxide secretion in response to LPS. These results did not rely on cells being in direct contact with the material as similar effects were observed in the presence of BG S53P4-conditioned medium. Our findings link the immunomodulatory properties of BG S53P4 and macrophage metabolism, which improves our understanding of the mechanisms underlying the clinical efficacy of bioactive glasses. Graphical Abstract